DO WE STILL NEED A CONVENTION IN THE FIELD OF HARMONISATION OF THE INTERNATIONAL COMMERCIAL LAW? - A. Korzhevskaya (BRICS Law Journal, 2016)
The paper critically discusses the opinion of certain scholars that the use of multilateral treaties (conventions) in the field of harmonisation of international commercial law has been in a state of steady decline. They believe that traditional treaty law has been gradually replaced in recent years by softer methods of making international law, such as the use of restatements and model laws. Some scholars even claim that treaty law is dead or dying. The work assesses whether this view has reasonable grounds, providing an overview of the most prominent hard law and soft law harmonising instruments and outlining issues relating to the success of conventions, their advantages, drawbacks and tensions arising in this area. The paper suggests that conventions remain necessary where the third party or public interest are at stake, however, further improvements are needed to make conventions more successful instruments in international commercial law.